1990
DOI: 10.1073/pnas.87.24.9660
|View full text |Cite
|
Sign up to set email alerts
|

Stability and activity of human immunodeficiency virus protease: comparison of the natural dimer with a homologous, single-chain tethered dimer.

Abstract: Wilmington, DE 19880-0328 Communicated by John D. Roberts, September 10, 1990 ABSTRACT A single-chain tethered dimer of human immunodeficiency virus protease (HIV-PR) was produced by expression of a synthetic gene in Escherichia coli. The tethered dimer, which consists of two 99-amino acid HIV-PR subunits linked together by a pentapeptide, was isolated from inclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 22 publications
3
102
0
Order By: Relevance
“…The synthetic fluorescent cationic peptide substrate 2-aminobenzoyl-Ala-Thr-His-Gln-Val-Tyr-Phe(NO 2 )-Val-Arg-Lys-Ala (28) was incubated with truncated or full-length HERV-K10 at 25°C in an assay buffer containing 50 mM MES, pH 5.0, 1 M NaCl, 20% glycerol, 1 mM EDTA. The synthesis of the substrate has been described elsewhere (28). The enzymatic reaction was terminated with 0.2 M ammonium hydroxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic fluorescent cationic peptide substrate 2-aminobenzoyl-Ala-Thr-His-Gln-Val-Tyr-Phe(NO 2 )-Val-Arg-Lys-Ala (28) was incubated with truncated or full-length HERV-K10 at 25°C in an assay buffer containing 50 mM MES, pH 5.0, 1 M NaCl, 20% glycerol, 1 mM EDTA. The synthesis of the substrate has been described elsewhere (28). The enzymatic reaction was terminated with 0.2 M ammonium hydroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Purification of HIV-1 Protease-HIV-1 protease was expressed in E. coli and then renatured from inclusion bodies as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…It also impairs immune function and the release of cytokines and growth factors, hindering the progression of inflammation and scarring 24 . In addition, hypothermia reduces the recruitment and function of neutrophils and the production of natural killer cells 25 , thereby decreasing antibody-mediated cell damage. In this study, we found that perioperative hypothermia reduced the activity of antioxidant enzymes in tissues from colonic anastomoses in rats.…”
Section: Level Of Lipid Peroxidation (Tbars)mentioning
confidence: 99%
“…The gene construct coded for two copies of the HIV monomer linked by the nucleotide sequence that codes for Gly-Gly-Ser-Ser-Gly. 48, 51 The nucleotide sequence that coded for each monomer was unique; the use of two different sequences allowed for site-directed mutagenesis to be targeted to a specific monomer. Cysteines at positions 67, 95, 167, and 195 were mutated to Leu, Met, Leu, and Met, respectively.…”
Section: Mutagenesis Protein Purification and Crystallizationmentioning
confidence: 99%
“…Therefore, all experimental data was collected using single chain HIV-1 protease in which the two monomers were tethered with a five amino acid flexible linker (GGSSG). [48][49][50][51] Kinetic experiments for the WT and Pr3 protease were carried out and resulting kinetic parameters for substrate cleavage were compared. Because of minimal peptide solubility, limited data was obtained for substrates with K M s >50 lM.…”
Section: Experimental Determination Of Binding and Kinetic Parametersmentioning
confidence: 99%